ANALISIS PENGARUH PERILAKU PEMIMPIN DAN REWARD TERHADAP PRESTASI KERJA KARYAWAN DI PT MEGA JAYA NET PANGKALPINANG - Joni, Belasius Deditus; Lestari, Deara Shinta; Novika (Jurnal Progresif Manajemen Bisnis, 2023)
The purpose of this study was to examine the influence of leader behavior and rewards on employee performance at PT Mega Jaya Net Pangkalpinang. This investigative methodology is quantitative. This study used a sample size of 45 from the employee population of PT Mega Jaya Net Pangkalpinang. Questionnaire-based data collection methods and surveys. Multiple linear regression analysis, F test, t test, and determination test were used to statistically analyze the data with the help of the JASP 0.16.2.0 program.